Exploring Integration Mechanism of Music Instructional Design and Education Informatization - Wang, Chenchen (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: In the new era of information society, the knowledge reform of school music education is getting more and more attention. Traditional teaching methods need to make full use of information technology. They cannot meet the current learning needs because the learning of information technology teaching is an essential means to realize modern learning. , therefore, the application of information technology in music education meets the requirements of the times. OBJECTIVES: To improve traditional teaching methods by utilizing modern teaching techniques so that students can gain more knowledge. With the help of modern technology and information technology, secondary music education can change the students’ audiovisual experience, enrich their musical experience, and deepen their understanding and memorization of knowledge. METHODS: In this paper, use a neural network algorithm to explore the integration mechanism of music teaching design and education information technology, optimize the traditional information technology teaching platform, improve the stability of the music teaching platform, and further improve the level of network teaching from the feedback of students and teachers. RESULTS: This study’s results found that this experiment’s educational platform could motivate students to manage teaching and actively participate in music teaching and lessons. However, due to the real-time nature of information technology, it removes doubts between the parties and facilitates communication between teachers and students. The primary goal of music education is to perceive the attraction of music in terms of sight and sound, to relax the mind and body, and to develop a musical personality. From this perspective, it is also necessary to utilize modern information technology to change teachers’ traditional teaching methods in classical performance and singing. CONCLUSION: With the help of modern technology and information technology, secondary music education can change the audiovisual experience of students, enrich their musical experience, and deepen their understanding and memorization of knowledge. The information system can motivate students to manage teaching and actively participate in music teaching.